Regionaal Particularisme en Staatsvorming in Afrika: De Diola van Zuid Senegal in hun Relatie Met Dakar. - Eichelsheim, John (Afrika Focus, 1991)
In the French daily newspaper "Libération" of 8/9september 19901 read : "Reveil de la guerilla en Casamance. Two clashes occurred between the Senegalese army and MFDC guerillas on the 22th of august and the 4th of september; 16 soldiers and 24 guerillas were killed". A morbid déjà vu. At the end of1983, as I did my practical training in the town of Ziguinchor, in the south of Senegal, I witnessed some fierce clashes between the same participants, causing the death of some 200 people. How could this be happening in one of the most democratic states of Africa? Didn't the political arena of some 16 different parties give enough room for oppositional currents? The answer must be negative, in some cases. In this paper I want to show the reader that the articulation of local organizational structures and development policies of a modern state can cause many problems. In this case the typical dynamics of the Diola society in southern Senegal and the specific way of state formation in Senegal after Independence form an explosive mixture. In the first part of the paper a description is given of the dynamics of the Diola society by portraying the organizational structures in Diola villages before the colonial period. Then, in the colonial period, due to new influences as a result of the contacts with foreigners, some local organizational structures are politicized. Among the Diola this process of politicizing took place on a very low level because the Diola society has all the characteristics of a segmentary society. Each village formed an autonomous unit headed by elders. The use of power lays in the hands of a group rather than in the hands of an individual. For this reason the Diola never fully participated in the political arena, not even after Independence. After Independence in 1960 the regimes in Dakar tried to impose their authority in all parts of the new state. First Leopold Senghor and then Abdou Diouf strived to form an omnipotent political party. A party in which all regional, ethnic and professional currants would be represented. This became the Parti Socialiste (PS). In the traditionally hierarchically organized societies in the North and the East of the state this was done by encapsulating powerful individuals. Once they joined the party they would bring along many followers or dependants as new members. But in the segmentary Diola society those political leaders did not exist. Therefore some individuals were dropped in the region by the PS to represent the inhabitants. These strangers were given a lot ofpower in the region. But it should be clear that these "representatives" were not accepted by local people who had the feeling of being colonized for the second time. This time by fellow countrymen from the North. For the Dakar regimes, a way to impose their hegemony was connected to the say over land ownership. Since the adaption of the National Lands Act on the 17th of June 1964, all transactions concerning the control over land must be regulated via the local governments. One of the main consequences of this reform is that the state becomes the sole landlord of all the land. This implies that local, mostly ancient, land tenure systems have formally ceased to exist. With the case of the explosive growth of the city of Ziguinchor I show the impact of this reform on the surrounding Diola society. As control over local land is the crux of the organizational structures of Diola society, this new intrusion of the state caused an emotional reaction. Moreover because it was mostly done at random by politicians who had only eyes for their own goals. This being the result of the specific way the state strived for hegemony and attempted to graft new forms of organization on the segmentary Diola society. With explosively results! KEYWORDS: Diola, politics, Senegal, social organisation, state formation, urban development